Risk mitigation in supply chain management process: procurement using house of risk method at PT. Pertamina EP Asset 4 - Wiwik Handayani; Syahda Elma Rabihah (Jurnal Siasat Bisnis, 2022)
Purpose: The purpose of this research is to identify and manage risks in the procurement of goods and services at PT. Pertamina EP Asset 4. The procurement process is an important thing that might affect the business processes of a company, therefore risk management is required to avoid obstacles and problems in a company.Design/methodology/approach: This study uses House of Risk method, where the risks are identified through mapping the procurement process of goods and services. Employing a descriptive approach with mixture of qualitative and quantitative, through questionnaires and interviews as well as data processing from the HOR method using Microsoft excel.Findings: The findings in this study contain mitigation action strategies sorted by implementation where appropriate to the needs and resources of the company so that the identified risks can be prevented as much as possible.Research Limitation/implication: in this study, the method used ignores the dependency between risk events in fact dependency can occur. It is expected that in the study of the continued can be taken into account.Practical Implication: Risk is inevitable but can be minimized, identifying risks with risk management is periodically needed to initiate changes in procurement that can pose other risks.Originality/Value: In this study identified several mitigation recommendations that are sorted from the difficulty level of implications so that companies can reduce the incidence of risks in procurement by providing a new outlook in accordance with the characteristics of risk.